Adherence to the Mediterranean diet and grade group progression in localized prostate cancer: An active surveillance cohort. Issue 5 (7th January 2021) - Gregg, Justin R.; Zhang, Xiaotao; Chapin, Brian F.; Ward, John F.; Kim, Jeri; Davis, John W.; Daniel, Carrie R.
Abstract : Background: The Mediterranean diet (MD) may be beneficial for men with localized prostate cancer (PCa) on active surveillance (AS) because of its anti‐inflammatory, antilipidemic, and chemopreventive properties. This study prospectively investigated adherence to the MD with Gleason score progression and explored associations by diabetes status, statin use, and other factors. Methods: Men with newly diagnosed PCa on an AS protocol (n = 410) completed a baseline food frequency questionnaire, and the MD score was calculated across 9 energy‐adjusted food groups. Cox proportional hazards models were fit to evaluate multivariable‐adjusted associations of the MD score with progression‐free survival; progression was defined as an increase in the Gleason grade group (GG) score over a biennial monitoring regimen. Results: In this cohort, 15% of the men were diabetic, 44% of the men used statins, and 76 men progressed (median follow‐up, 36 months). After adjustments for clinical factors, higher adherence to the MD was associated with a lower risk of GG progression among all men (hazard ratio [HR] per 1‐unit increase in MD score, 0.88; 95% confidence interval [CI], 0.77‐1.01), non‐White men (HR per 1‐unit increase in MD score, 0.64; 95% CI, 0.45‐0.92; P for interaction = .07), and men without diabetes (HR per 1‐unit increase in MD score, 0.82; 95% CI, 0.71‐0.96; P for interaction = .03). When joint effects of the MD score and statin use were examined, a similar risk reduction was observed among men with high MD scores who did not use statins in comparison with men with low/moderate MD scores with no statin use. Conclusions: The MD is associated with a lower risk of GG progression in men on AS, and this is consistent with prior reports about the MD and reduced cancer morbidity and mortality. Abstract : The association of Mediterranean diet adherence and grade group progression was evaluated in a prospective cohort of patients with localized prostate cancer managed according to a clinical protocol. Mediterranean diet adherence may be associated with improved progression‐free survival.